Implementasi Pendidikan Literasi di Wilayah Azzainiyah, Pondok Pesantren Nurul Jadid - Irma Sari Fadillah; Wiwin Warliah (MANAZHIM, 2022)
The era of modern technology requires its residents to pursue competence and competitiveness. Therefore, education is needed by humans as a basic need in developing competitiveness to achieve a glorious future. It also makes a person need literacy education for competence, accuracy, determination, trustworthiness, courage to face the risks of every decision he chooses and so on. The reality is that many Islamic boarding schools have not achieved the competencies desired by these institutions. This is traced to the fact that there are still many pesantren graduates who cannot play a role in society as a developer of religious or non-religious knowledge. This research was conducted with the aim of explaining how the implementation of literacy education in the Az-Zainiyah area of ​​the Nurul Jadid Islamic boarding school was carried out as a form of effort to face the challenges of modern times in the future. This study uses a qualitative approach. Data collection techniques using observation, interviews and documentation. The research subjects consisted of one head of the Az-Zainiyah region, four coordinators of the Az-Zainiyah student literacy forum, one female student and one female student. The data analysis technique uses data reduction that has been collected, data presentation, and drawing conclusions and observations. The results showed that the implementation of literacy education in the Az-Zainiyah region was carried out by learning and studying the yellow book, book bazaars, talents and interests, competitions on literacy, and short studies, namely a seven-minute lecture. However, in the implementation of these various forms of literacy, there are obstacles, namely there is no free forum to express the literary works of students, the lack of books that are of interest to students, and the lack of motivation of students from their respective administrators.